Inducing and Administering Tregs to Treat Human Disease - Perdigoto, Ana Luisa; Chatenoud, Lucienne; Bluestone, Jeffrey A.; Herold, Kevan C. (Frontiers in Immunology, 2016)
Regulatory T cells (Tregs) control unwanted immune responses, including those that mediate tolerance to self as well as to foreign antigens. Their mechanisms of action include direct and indirect effects on effector T cells and important functions in tissue repair and homeostasis. Tregs express a number of cell surface markers and transcriptional factors that have been instrumental in defining their origins and potentially their function. A number of immune therapies, such as rapamycin, IL-2, and anti-T cell antibodies, are able to induce Tregs and are being tested for their efficacy in diverse clinical settings with exciting preliminary results. However, a balance exists with the use of some, such as IL-2, that may have effects on unwanted populations as well as promoting expansion and survival of Tregs requiring careful selection of dose for clinical use. The use of cell surface markers has enabled investigators to isolate and expand ex vivo Tregs more than 500-fold routinely. Clinical trials have begun, administering these expanded Tregs to patients as a means of suppressing autoimmune and alloimmune responses and potentially inducing immune tolerance. Studies in the future are likely to build on these initial technical achievements and use combinations of agents to improve the survival and functional capacity of Tregs.